Profitability of Saudi Commercial Banks: A Comparative Evaluation between Domestic and Foreign Banks using CAMEL Parameters - Saif-Alyousfi, Abdulazeez Y.H.; Saha, Asish; Md-Rus, Rohani (International Journal of Economics and Financial Issues, 2017)
Recent banking reforms in Saudi Arabia fostered the entry of foreign banks to increase competition and improve the financial stability of the Saudi banking sector. There is, however, no comprehensive econometric study which has analysed the profitability of domestic and foreign banks on a standalone and comparative basis. Present paper fills in this gap and assesses the profitability of Saudi banks using the parameters of the CAMEL framework over the period 2000-2014 using pooled OLS and fixed effect model. Our results indicate that domestic banks are more profitable than foreign banks. We also find that both foreign and domestic banks with higher capital are more profitable. Banks with a higher non-performing loan are less profitable: foreign banks carry more credit risk in their portfolio. In contrast to domestic banks, operating expenses to total income for foreign banks is significant but negatively related to profitability, indicating that cost management inefficiency adversely affect the profitability of this group. Our results also indicate that banks with larger size are less profitable. We also find that steep rise in lending activities lead to increase in the profitability of domestic banks but has adversely affected the profitability of foreign banks in the country. The findings of the study have many policy implications. Keywords: Profitability, Foreign banks, Domestic banks, CAMELs model, Saudi Arabia JEL Classifications: G20; G21, G01, G24, C23; L25, E40, O16